Stroma in normal and cancer wound healing. (15th April 2019) - Huet, Eric; Jaroz, Camille; Nguyen, Hoang Quy; Belkacemi, Yazid; de la Taille, Alexandre; Stavrinides, Vasilis; Whitaker, Hayley
Abstract : It is currently believed that stroma, the connective framework of biological tissues, plays a central role in normal wound healing and in cancer. In both these contexts, stromal cellular components such as activated fibroblasts interact with complex protein networks that include growth factors, structural protein or proteinases in order to initiate and sustain an extensive remodelling process. However, although this process is usually spatially and temporally self‐limited, it is unregulated in the case of cancer and leads to uncontrolled cell proliferation and invasion within tissues, metastasis and therapeutic resistance. In this review, we outline the role of stroma in normal healing, cancer and post radiotherapy, with a particular focus on the crosstalk between normal or cancer cells and fibroblasts. Understanding these mechanisms is particularly important as several stromal components have been proposed as potential therapeutic targets. Abstract : Stromal modification, a key step in the control of wound healing, tumour progression and radiation‐induced fibrosis, is characterized by the differentiation of quiescent fibroblasts into an activated state, which results in crosstalk among fibroblasts and normal or cancer cells. Understanding these activation mechanisms, which involve extracellular matrix metalloproteinase inducer and transforming growth factor beta, is important because several stromal components are potential therapeutic targets.